2011
DOI: 10.1111/j.1471-0307.2011.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterisation of Lactobacilli isolated from camel cheese produced in India

Abstract: Thirty‐two Lactobacilli strains were isolated from four samples of camel cheese collected from Bikaner, India. These isolates were identified based on phenotypic and genotypic characteristics. Sequencing of 16S rDNA was performed for species identification and diversity analysis. Lactobacillus delbrueckii and Lb. fermentum were found to be dominant species followed by Lb. plantarum and Lb. casei. On evaluation of technological properties of these isolates, 20 isolates were observed to be good acid producers, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Isolation of L. plantarum strains have been carried out from different traditional cheese products, for instance several Iranian and Italian cheese varieties [22], Polish golka cheese [23], Greek Melichloro cheese [24], Turkish Karin Kaymak cheese [25], Serbian Zlatar cheese [26], Indian camel cheese [27], Brazilian ovine cheese [28], Tibetan Qula cheese [29], and West African soft cheese [30]. The key motive of the current assessment was to explore the antimicrobial potentials of L. plantarum spp., isolated from Hurood cheese, which is a conventional type of hard cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of L. plantarum strains have been carried out from different traditional cheese products, for instance several Iranian and Italian cheese varieties [22], Polish golka cheese [23], Greek Melichloro cheese [24], Turkish Karin Kaymak cheese [25], Serbian Zlatar cheese [26], Indian camel cheese [27], Brazilian ovine cheese [28], Tibetan Qula cheese [29], and West African soft cheese [30]. The key motive of the current assessment was to explore the antimicrobial potentials of L. plantarum spp., isolated from Hurood cheese, which is a conventional type of hard cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion with the bacterial powder preparation of L. plantarum or cheese containing L. plantarum (10.0 log CFU per day for 3 weeks) was found to be safe [52]. Recently, L. plantarum strains have been isolated in a wide variety of traditional cheese products, such as different Italian and Iranian cheese varieties [9], Greek Melichloro cheese [42], Polish golka cheese [51], Serbian Zlatar cheese [56], Turkish Karin Kaymak cheese [55], Tibetan Qula cheese [17], Indian camel cheese [40], Brazilian ovine cheese [38], and West African soft cheese [4].…”
Section: Introductionmentioning
confidence: 99%
“…Camel milk creams have a healing effect on skin autoimmune diseases. Phenotypic and genotypic characterization of lactobacilli isolated from camel milk cheese produced by NRC on Camel, Bikaner, revealed that these isolates have potential for development of defined strain starter for camel cheese [82].…”
Section: Development Of Camel Milk Productsmentioning
confidence: 99%